General Practice Patterns and Workload Distribution, B.C. Optometrists Core Group - Samek, M.J; Schmidt, B.T (Canadian Journal of Optometry, 1980)
A government-appointed task force in British Columbia investigated and made recommendations on the delivery of vision care services in that province. Alternative means of delivery were considered within role definitions of optometrists and ophthalmologists and their respective workloads.